Big data analytics in traffic and transportation engineering : emerging research and opportunities - Moridpour, Sara, 1980- (Hershey, PA : Engineering Science Reference, an imprint of IGI Global, 2019)
'This book identifies the factors contributing to the severity of vehicle-pedestrian crashes at mid-blocks. It examines the influence of the socioeconomic factors of the neighborhoods where road users live (residency neighborhood) and where crashes occur (crash neighborhood) on vehicle-pedestrian crash severity, while controlling for the influences of roadway, road user, vehicle and environmental factors'--Provided by publisher.
Access to public transport in metropolitan areas -- Bikeability in metropolitan areas -- Walkability in metropolitan areas -- Applying decision tree approaches on vehicle-pedestrian crashes -- Neighbourhood influences on vehicle-pedestrian crash severity -- Spatial and temporal distribution of pedestrian crashes -- Contributing factors on vehicle-pedestrian crash severity of school-aged pedestrians.
Includes bibliographical references (pages 164-185) and index.
Keywords: Pedestrian accidents -- Australia -- Melbourne (Vic.) -- Statistical methods; Traffic accidents -- Australia -- Melbourne (Vic.) -- Statistical methods; Roads -- Interchanges and intersections -- Safety measures -- Statistical methods; Big data -- Australia -- Melbourne (Vic.)